In Defense of Methodological Naturalism - McDonald, Patrick ca. 20./21. Jh. (Christian scholar's review, 2009)
In this paper, Patrick McDonald and Nivaldo J. Tro argue that all scientists, including theists, should practice science in accord with methodological naturalism, the idea that scientific theories should be naturalistic (they should not contain supernatural elements). They present several reasons for accepting methodological naturalism, including its proven historical success, and they argue also that such a practice need not imply metaphysical naturalism (the idea that only the natural exists). In fact, they suggest that there might be good theological and apologetic reasons to accept methodological naturalism. Mr. McDonald is Associate Professor of Philosophy at Seattle Pacific University and Mr. Tro is Professor of Chemistry at Westmont College.